Use of linear radiofrequency device in liver resection - Stojanović Miroslav P.; Radojković Milan; Stanojević Goran (Vojnosanitetski Pregled)
Background/Aim. Linear radiofrequency device (LRFD) is disposable tool designed for liver parenchyma transection using controlled radiofrequency to 'seal' blood vessels and bile ducts, making liver resection easier and safer compared to classical resectional techniques. The aim of this study was to determine real value of the LRFD compared to the standard 'keliclasia' technique. Methods. This prospective study analyzed the significant intraoperative parameters and postoperative results of the 200 patients who underwent surgery at the Surgery Clinic of Clinical Centre in Niš, between January 1, 2001, and January 1, 2009. The patients were divided into two groups: the control Keli group (144 patients) with the 'keliclasia' resection technique and the control RF group (with resection performed using LRFD - Tissue Link / Dissection Sealer (DS - 3.0) (56 patients). The following parameters were analyzed: duration of liver ischemia, liver parenchyma transection time, intraoperative blood loss, significant intraoperative and postoperative complication rate, duration of hospitalization and mortality. Results. LRFD was used in 56 liver resections. The average duration of liver ischemia in the RF group was shorter than in the Keli group (7 versus 22 minutes). Parenchymal liver transection was significantly slower in the RF group than in the Keli group (2.05 versus 4.34 cm2/minutes, respectively). There was less intraoperative bleeding using LRFD 'Keliclasia' tehniquethan in the control group (390 mL compared to 420 mL, respectively). After the use of LRFD two cases of biliary leak and 4 pleural effusions were registered. Conclusion. LRFD is simple device for safe liver transection with decreased need for liver ischemia and singificant reducing of the intraoperative blood loss. High price for disposable device and slow parenchyma transection are disadvantages of this device.